2016
DOI: 10.1177/1357633x16648490
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance-based assessment of NIH Stroke Scale with telemedicine: A feasibility pilot study

Abstract: Background Ischemic stroke is a time-sensitive disease, with improved outcomes associated with decreased time from onset to treatment. It was hypothesised that ambulance-based assessment of the National Institutes of Health Stroke Scale (NIHSS) using a Health Insurance Portability and Accountability Act (HIPAA)-compliant mobile platform immediately prior to arrival is feasible. Methods This is a proof-of-concept feasibility pilot study in two phases. The first phase consisted of an ambulance-equipped HIPAA-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 13 publications
(16 reference statements)
0
63
0
1
Order By: Relevance
“…Technologies employed by included studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] were best described using three categories: blood biomarkers [22,23]; pre-hospital imaging [24,25] and mobile telemedicine/telestroke (including transfer of audio and/or visual information or relevant data) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These are summarised in Table 1. Most studies were conducted in the USA [24,26,27,[34][35][36][37][38][39], followed by Germany [28]…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Technologies employed by included studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] were best described using three categories: blood biomarkers [22,23]; pre-hospital imaging [24,25] and mobile telemedicine/telestroke (including transfer of audio and/or visual information or relevant data) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These are summarised in Table 1. Most studies were conducted in the USA [24,26,27,[34][35][36][37][38][39], followed by Germany [28]…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…119 More recent studies examined the paradigm again and showed that the transmission of video data reached acceptable levels of quality and reliability. 118,120 However, the most compelling evidence comes from the STEMO (Stroke Emergency Mobile) project in Berlin in which the use of a mobile stroke unit with onboard neurologist but remote teleradiologist has led to more rapid alarm-to-needle times with no increase in the rate of complications and improvement in outcomes estimated at €32 456 per quality-adjusted life-year. 121,122 In the United States, several ongoing pilot studies of mobile stroke units suggest that the model is robust and that a teleneurologist may be able to substitute for an onboard neurologist.…”
Section: Mobile Stroke Unitsmentioning
confidence: 99%
“…118 Early attempts at mobile ambulance-based telehealth were hampered by inadequate bandwidth and reliability, but recent advances in telecommunications technology have enabled newer more robust solutions. The TeleBAT intervention from the team at University of Maryland used wireless cellular technology in ambulances to transmit visual and auditory data to a stroke neurologist in real time at very low frame rates and was neither practical nor scalable.…”
Section: Mobile Stroke Unitsmentioning
confidence: 99%
“…While the inspection component of physical examination performed via visual telecommunication devices has been validated,58 – 60 the main limitation of the technology remains the inability of the remote operator to complete full physical examination. We overcame this by a team approach, with an NCHD accompanying the robot and examining where indicated.…”
Section: Discussionmentioning
confidence: 99%